Biochemical Parameters and Protein Oxidation Relationship for Hepatitis C Patients and Healthy Ones: Protien Oxidation Uses for Hepatitis C Patients (Biological Sciences - PJSIR, 2022)
Globally hepatitis C virus is recognized as one of the basic health issues of liver and result in chronic liver diseases whose diagnosis is difficult and possible only with symptoms until it may leads to liver cancer. DNA damage along with lipids and protein oxidation is caused as result of oxidative stress in hepatitis patients. This work was carried out to search out the oxidation of protein and lipids per-oxidation with relative to DNA damage for hepatitis C patients. Sampling was done in 50 suspected patients among them 20 were positive for HCV, while 30 were negative. With the help of 2-4, dinitrophenyl hydrazine assay quantification of protein carbonyls was done and results showed much increased values than normal. Biochemical parameters of HCV such as complete blood count, triglycerides and cholesterol level were recorded. The results were significant in positive cases than the control group. The study elaborated a new window in the research of chronic HCV patients for severe biochemical parameters alterations, over oxidation of proteins and liver dysfunction. It was therefore concluded that oxidative stress was responsible for increased level of protein oxidation and altered biochemical parameters that leads to damage of liver